Hubungan tingkat stres dengan asupan gizi makro pada mahasiswa masa new normal - Maharani, Feiga; Saleh, Asep Jalaludin; Nurhartanto, Adhi (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: The condition that arises when someone faces a threatening situation that results in emotional and physiological disorders, and has an impact on the inability to carry out daily activities is called stress. During the COVID-19 pandemic, the learning process involves the use of technology and distance learning methods, making students experience anxiety and stress. Macronutrients play an important role in preventing disease and improving health. To increase optimal body resistance during the COVID-19 pandemic, it is recommended to have a balanced and nutritious diet. Purpose: To investigate the relationship between stress levels and macronutrient food intake in college students. Method: The study used a quantitative approach with a cross-sectional design in second semester students of UMITRA Lampung. The DASS (Depression Anxiety Stress Scale) 42 questionnaire, 3x24-hour Food Recall Form, and macronutrient intake with the Nutrisurvey application were the instruments applied in this study. Data processing and analysis were carried out using univariate and bivariate analysis. Bivariate analysis used the Chi-Square statistical test with a degree of confidence interval and error rate (a = 0.05). Results: The Chi-square statistical test showed no significant correlation between stress levels and macronutrient intake with ρ-value results of 1.000 for stress levels and energy intake, 0.517 for stress levels and carbohydrate intake, 1.000 for stress levels and protein intake, and 0.615 for stress levels and fat intake. Conclusion: There is no significant correlation between students' stress levels and food intake containing macronutrients (energy intake, carbohydrate intake, protein intake, and fat intake) Keywords : Macronutrients; New Normal; Stress Level; Students Pendahuluan: Kondisi yang timbul ketika seseorang menghadapi situasi yang mengancam sehingga mengakibatkan gangguan emosi, fisiologis, serta berdampak pada ketidakmampuan dalam menjalani kegiatan sehari-hari disebut sebagai stres. Pada masa pandemi COVID-19, proses pembelajaran melibatkan pemanfaatan teknologi dan metode jarak jauh menjadikan mahasiswa mengalami kegelisahan dan tekanan. Gizi makro memainkan peran penting dalam mencegah penyakit dan meningkatkan kesehatan. Meningkatkan resistensi tubuh yang optimal selama pandemi COVID-19, disarankan untuk melakukan pola makan yang seimbang dan kaya nutrisi Tujuan: Untuk menginvestigasi hubungan antara tingkat stres dan asupan makanan yang mengandung nutrisi makro pada mahasiswa. Metode: Penelitian menggunakan pendekatan kuantitatif dengan desain potong lintang pada mahasiswa semester II UMITRA Lampung. Kuesioner DASS (Depression Anxiety Stress Scale) 42, Food Recall Form 3x24 jam, dan asupan gizi makro dengan aplikasi Nutrisurvey adalah Instrumen yang diterapkan pada penelitian ini. Pengolahan dan penganalisaan data dilakukan dengan analisis univariat dan bivariat. Penganalisaan bivariat menggunakan uji statistik Chi-Square dengan derajat kepercayaan confidence interval dan tingkat kesalahan (a=0.05). Hasil: dari uji statistik Chi-square menunjukkan tidak adanya korelasi yang berarti antara tingkat stres dan asupan zat gizi makro dengan hasil ρ-value yaitu 1,000 untuk tingkat stres dan asupan energi, 0,517 untuk tingkat stres dan asupan karbohidrat, 1,000 untuk tingkat stres dan asupan protein, serta 0,615 untuk tingkat stres dan asupan lemak. Simpulan: Tidak ada korelasi yang signifikan antara tingkat stress mahasiswa dengan asupan makanan yang mengandung nutrisi makro (asupan energi, asupan karbohidrat, asupan protein, dan asupan lemak). Kata Kunci : Gizi Makro; Mahasiswa; New Normal; Tingkat Stres